Climbers’ Behavior in Reducing Environmental Damage at Mount Batur - Trikayanti, Kadek Holy Campala; Mudana, I Gede; Oka, I Made Darma; Chaerunnisah, Indah Utami; Sudiarta, Made (Jurnal Bali Membangun Bali, 2023)
Purpose: This study aims to determine behavior of climbers and to find out the efforts made by the tracking manager to minimize environmental damage caused by climbing or tracking activities as well as maintaining personal safety for climbers in Mount Batur area, Bangli, Bali. Research methods: This study used a qualitative descriptive method. Apart from being a literature study, this research uses observation, in-depth interviews, and documentation. Result and discussion: The results of the study show that the climbers who often say they are nature lovers have awareness of environmental sustainability starting from being aware of the garbage around and complying with the regulations that have been made by the manager to avoid environmental damage and maintain their own safety so that unwanted events in the climbing process can be avoided. Implications: The results of this study are expected to be used as parameters in decision making for the managers of the Mount Batur area and it is also hoped that climbers can jointly maintain and comply with existing regulations for the preservation of this mountain.